Muzeji in družbeno vključevanje - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2011)
The article presents new developments in the activities of museums related tosocial inclusion. It describes several exhibitions promoting social inclusion in Slovene museums and galleries, while particular attention is dedicated to the exhibition Life in the streets - on homelessness in Slovenia, which the Slovene Ethnographic Museum staged to inform the public on the issues of homelessness and include people with experience of homelessness in the preparation of the exhibition and, indirectly, in the wider society.
Keywords: museums; Slovenski etnografski muzej; social role; Ljubljana; Družbeni vidik; exhibition themes and motives; homeless persons; muzeji; družbena vloga; razstave; brezdomci